Growth development and yield of Melientha suavis pierre in Southern Thailand (Thai) - Chiarawipa, Rawee; Keawdoung, Montree; Tanpanich, Sayan (Asia-Pacific Journal of Science and Technology, 2017)
The growth and yield of Melientha suavis Pierre under intercropping of vegetable hummingbird (Sesbania grandiflora L.) was studied at Songkhla province. Forty 5-month-old seedlings were randomly sampled to measure physiological responses, growth rate and shoot weight in 2007-2009. The results showed that the plasticity in physiological responses (photosynthesis, transpiration, stomatal conductance and chlorophyll concentration) was advantageous under the experimental conditions. Annual growth rate for height (60.23 cm), canopy width (57.71 cm) and trunk diameter (1.89 cm) had a rapid increase, than growth rates in 2nd year. Shoot length and leaf area development remained stable after 21 days of emergence of new shoots which positively occurred in January to April and September to October. However, shoot weight was at a peak in March (205.51 g tree-1). Further studies are needed to accelerate shoot emergence to produce high-yield potential.